Genome- and epigenome-wide association study of hypertriglyceridemic waist in Mexican American families. Issue 1 (December 2016) - Mamtani, Manju; Kulkarni, Hemant; Dyer, Thomas; Göring, Harald; Neary, Jennifer; Cole, Shelley; Kent, Jack; Kumar, Satish; Glahn, David; Mahaney, Michael; Comuzzie, Anthony; Almasy, Laura; et al.
Abstract Background There is growing interest in the hypertriglyceridemic waist (HTGW) phenotype, defined as high waist circumference (≥95 cm in males and ≥80 cm in females) combined with high serum triglyceride concentration (≥2.0 mmol/L in males and ≥1.5 mmol/L in females) as a marker of type 2 diabetes (T2D) and cardiovascular disease. However, the prevalence of this phenotype in high-risk populations, its association with T2D, and the genetic or epigenetic influences on HTGW are not well explored. Using data from large, extended families of Mexican Americans (a high-risk minority population in the USA) we aimed to: (1) estimate the prevalence of this phenotype, (2) test its association with T2D and related traits, and (3) dissect out the genetic and epigenetic associations with this phenotype using genome-wide and epigenome-wide studies, respectively. Results Data for this study was from 850 Mexican American participants (representing 39 families) recruited under the ongoing San Antonio Family Heart Study, 26 % of these individuals had HTGW. This phenotype was significantly heritable (h 2 r = 0.52, p = 1.1 × 10−5 ) and independently associated with T2D as well as fasting glucose levels and insulin resistance. We conducted genome-wide association analyses using 759, 809 single nucleotide polymorphisms (SNPs) and epigenome-wide association analyses using 457, 331 CpG sites. There was no evidence of any SNP associated with HTGW at the genome-wide level but two CpG sites (cg00574958 and cg17058475) inCPT1A and one CpG site (cg06500161) inABCG1 were significantly associated with HTGW and remained significant after adjusting for the closely related components of metabolic syndrome.CPT1A holds a cardinal position in the metabolism of long-chain fatty acids whileABCG1 plays a role in triglyceride metabolism. Conclusions Our results reemphasize the value of HTGW as a marker of T2D. This phenotype shows association with DNA methylation withinCPT1A andABCG1, genes involved in fatty acid and triglyceride metabolism. Our results underscore the importance of epigenetics in a clinically informative phenotype.